The prevalence of subclassification-based diagnoses when considering cervical contribution in shoulder pain patients: a secondary analysis from a previous research - Roldán-Ruiz, Alberto; Bailón-Cerezo, Javier; Torres-Lacomba, María (The Journal of manual & manipulative therapy, 2025)
Determining the prevalence of different shoulder subclassification-based diagnoses using a defined exclusion-type diagnostic algorithm. Analyzing the relationships between cervical contribution and other shoulder diagnoses. A proposal of a shoulder pain diagnosis based on functional subclassification was carried out in all subjects. The included diagnoses were cervical contribution, acromioclavicular joint pain, stiff shoulder, atraumatic unstable shoulder, rotator cuff-related shoulder pain, and 'Others'. Each diagnosis was based on a defined exclusion-type diagnostic algorithm. Cervical contribution was considered if a > 30% shoulder symptom modification in pain intensity was recorded after a cervical spine screening. Since a > 30% change in symptoms does not definitively indicate a categorical diagnosis, cervical contribution was presumed to potentially coexist with other diagnostic labels in these cases. If there was a complete (100%) resolution of shoulder symptoms after the cervical spine screening, cervical contribution was deemed the sole diagnosis. Sixty subjects were analyzed. Rotator cuff-related shoulder pain was the most prevalent diagnosis (36.7%, = 22), followed by stiff shoulder, being present in 30% ( = 18) of subjects. Cervical contribution (13.3%, = 8), atraumatic unstable shoulder (11.7%, = 7), others (6.7%, = 4) and acromioclavicular joint pain (1,7%, = 1) completed the results. In patients diagnosed with rotator cuff-related shoulder pain, cervical contribution coexisted in 71,4% of them. Thus, a statistically significant association between cervical contribution and rotator cuff-related shoulder pain was found ( = 0,002). This association was not observed in any of the other diagnoses. Rotator cuff-related shoulder pain was the most prevalent diagnosis, followed by stiff shoulder and cervical contribution. Cervical contribution may coexist with other diagnoses or even be considered as a unique diagnosis itself. Patients diagnosed with rotator cuff-related shoulder pain are more likely to have cervical contribution.